Copper Accumulation on Avicennia marina In Tapak, Tugurejo, Semarang, Indonesia - Nana Kariada Tri Martuti; Budi Widianarko; Bambang Yulianto (Diponegoro University, 2016)
Mangroves are good hyperaccumulators, they are not only able to grow on highly poisonous land, but also accumulate the poisonous substances in the branches and leaves. The aim of the research was to evaluate the bioaccumulation of Cu on Avicennia marina in Tapak Semarang. Tapak Semarang is selected as the research site because the mangrove ecosystem is surrounded by milkfish ponds. The research used ecological approach. Bioaccumulation data and heavy metal translocation in plants, sediment and water were analyzed using pre-determined formulation. Results showed that Cu was found in water (0.0069 mg/l), sediment (26.760-37.889 mg/Kg), roots (2.336-7.997 mg/Kg), young leaves (2.367-6.604 mg/Kg) and old leaves (1.080-6.748 mg/Kg) of Avicennia marina. Sediment have the highest ability to accumulate Cu ( ) compared to water with concentration factors of ranging from 3878.26 to 5491.16. The Bioconcentration Factor (BCF) of roots and sediment was ranging from 0.09 to 0.211, and the Translocation Factors (TF) for young leaves was ranging from 0.83 to 1.54 and for old leaves was ranging from 0.46 to 0.94. It was found that the concentration of Cu in the pond tended to increase towards the sea. It was concluded that there was an accumulation of Cu in the sediment, roots and leaves of Avicennia marina in Tapak, Tugurejo Semarang. The sediment have the highest ability to accumulate Cu from the environment.